Government Finance Statistics Yearbook, 2011. (Government Finance Statistics; Government Finance Statistics ;, 2012)
The IMF Government Finance Statistics contains statistical data on government financial operations for 156 countries. Where reported, the database contains time series from 1990 onwards using the Government Finance Statistics Manual 2001 (GFSM 2001) framework. The statistics, issued quarterly, are updated as new data are received and time series become available. These time series present combined statistics on revenue, expense, transactions in non-financial assets, and financial assets and liabilities, as well as on stocks of assets and liabilities of general government and its subsectors.